2016
DOI: 10.1007/s00404-016-4145-3
|View full text |Cite
|
Sign up to set email alerts
|

Expectant management versus multifetal pregnancy reduction in higher order multiple pregnancies containing a monochorionic pair and a review of the literature

Abstract: Fetal reduction in triplets and quadruplets including a monochorionic pair is associated with decreased early prematurity. While in quadruplets the overall survival is higher after reduction, there was no difference for dichorionic triplets with reduction or conservative management. Complications owing to monochorionicity are frequently observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…In the DC triplet pregnancies undergoing intrafetal laser, the rate of miscarriage (3%) was considerably lower than the reported rate in DC triplets managed expectantly (9%), and those having ER by KCl to monochorionic twins (13%) or singleton (18%). The rate of PTB at < 33 weeks' gestation was considerably lower with intrafetal laser (7%) than with expectant management (35%) or ER by KCl to monochorionic twins (13%), and it was similar to that of ER to singleton (9%).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the DC triplet pregnancies undergoing intrafetal laser, the rate of miscarriage (3%) was considerably lower than the reported rate in DC triplets managed expectantly (9%), and those having ER by KCl to monochorionic twins (13%) or singleton (18%). The rate of PTB at < 33 weeks' gestation was considerably lower with intrafetal laser (7%) than with expectant management (35%) or ER by KCl to monochorionic twins (13%), and it was similar to that of ER to singleton (9%).…”
Section: Discussionmentioning
confidence: 85%
“…In dichorionic (DC) triplet pregnancies, ER by KCl involves either the DC fetus or both monochorionic twins; the injected KCl to only one of the monochorionic twins could be transferred to the cotwin through the intertwin placental vascular anastomoses or death of one fetus could lead to hemorrhage from the cotwin into the dead fetoplacental unit with consequent death or neurodevelopmental impairment in the survivor. In DC triplet pregnancies, compared with TC triplets, there is a higher rate of miscarriage both with expectant management (9% vs 3%) and after ER to twins (13% vs 7%), which could, at least in part, be attributed to complications arising from intertwin placental vascular communications and/or unequal sharing of the placenta in the monochorionic pair.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Limited reports are available from studies of quadruplets in comparison, [10][11][12] and fewer reports are available on higher order multifetal pregnancy. 8,15,16 Many studies have reported higher order multifetal pregnancy reduction but often they are neither conducted in single centers nor performed by the same physician. Our study included a lager sample size of 131 patients comprising 104 sets of quadruplets, 20 sets of quintuplets, 5 sets of sextuplets, 1 set of septuplets, and 1 set of octuplets.…”
Section: Discussionmentioning
confidence: 99%
“…Abel and coworkers reported 40 cases of triplets, 10 cases of quadruplets, and no cases of quintuplets. 15 In the study by Fajolu et al, there were 15 cases of triplets, 6 cases of quadruplets, and only one case of quintuplets reported. 8 In another study, there were 35 cases of quadruplets, 11 of quintuplets, 1 of sextuplets, and 1 of septuplets reported.…”
mentioning
confidence: 95%
“…tient demographics, pregnancy and medical history to enable the prediction of chromosomal abnormalities [21], PE [22], and GDM [23] in twin pregnancy. In treating MC twins with TTTS -Prof. Nicolaides is a leading partner in the international group that develop ultrasound measures and intra uterine laser surgery procedures to save either both twins (50%) or at least one (75%), followed by establishing standards and teaching methods to disseminate this knowledge [25,26]. Dr. Giepel improved outcome by offering shunting procedures to reduce secondary complications [27].…”
Section: Develop a Differential Diagnosis And Predic-mentioning
confidence: 99%